AGRICULTURE AND FOOD SECURITY IN ROMANIA - Manole, Victor (Economics of Agriculture, 2012)
Theoretical definitions are given within the article regarding food security and independence and also there are presented the agents that influence them. Moreover, a description of the security at global and national level is given, illustrated by a series of specific indicators and trends of their evolution. Finally, it is described the perspective of food security in our country.